O papel do enriquecimento ambiental na preparação comportamental do papagaio-de-peito-roxo (Amazona vinacea) (Aves, Psittacidae) para reintrodução no Parque Nacional das Araucárias, SC - Martins, Mariana Herminio Bressan (Universidade Federal de São Carlos, 2020)
Brazil is the richest country of species for the Psittacidae family; however, due to the fragmentation and degradation of natural landscapes, coupled with illegal traffic, several species of this family present themselves at some level of threat, such as the vinaceous breasted parrot (Amazona vinacea). Since 2010, Instituto Espaço Silvestre has focused on reintroducing this specie, which was extinct in the area that currently houses the Araucárias National Park (PNA), in the state of Santa Catarina. Part of the success of reintroduction programs is due to the behavioral and physical conditions of the animals at the time of the release and after. The large majority of the individuals of these programs are from captivity, without precise information about age, past history etc. Offering opportunities for performance and development of natural behaviors in the rehabilitation period may increase individual’s survival rates after reintroduction. Our goal was to implement and evaluate the use of enrichments to enhance foraging and natural routine behaviors of vinaceous amazon parrots destined to reintroduction at PNA. The results indicated that the food enrichments used can be efficient in promoting podomandibulation, enabling the performance and balance of natural foraging behaviors. The podomandibulation time of araucária pine nuts increased after an enriched period. The parrots showed to be conditioned to routine training after fifty days (in total) of training, according to the time of the training. However, the animals did not stay overnight in the area designated as a dormitory, suggesting that further studies should be conducted to understand animal’s motivations in forming a communal roost. However, giving the possibility to demonstrate natural behaviors, and approaching the time budget of their wild conspecifics, contributes to the welfare of animals kept under human care.
The role of environmental enrichment in the behavioral preparation of the vinaceous amazon parrot (Amazona vinacea) (Aves, Psittacidae) for reintroduction in the Araucárias National Park, SC
Keywords: Amazona vinacea; Reintrodução; Enriquecimento; Rotina; Forrageamento; Reintroduction; Enrichment; Routine; Foraging; CIENCIAS BIOLOGICAS::ZOOLOGIA